Long Wavelength Approximation to Peristaltic Motion of Micropolar Fluid with Wall Effects (Advances in Applied Mathematics and Mechanics, 2010)
Peristaltic motion of an incompressible micropolar fluid in atwo-dimensional channel with wall effects is studied. Assumingthat the wave length of the peristaltic wave is large in comparisonto the mean half width of the channel, a perturbation method ofsolution is obtained in terms of wall slope parameter, under dynamicboundary conditions. Closed form expressions are derived for thestream function and average velocity and the effects of pertinentparameters on these flow variables have been studied. It has beenobserved that the time average velocity increases numerically withmicropolar parameter. Further, the time average velocity alsoincreases with stiffness in the wall.